Characterization of Interleukin-15-Transpresenting Dendritic Cells for Clinical Use - J. M. J. Van den Bergh; E. L. J. M. Smits; M. Versteven; H. De Reu; Z. N. Berneman; V. F. I. Van Tendeloo; E. Lion (Journal of Immunology Research)
Personalized dendritic cell- (DC-) based vaccination has proven to be safe and effective as second-line therapy against various cancer types. In terms of overall survival, there is still room for improvement of DC-based therapies, including the development of more immunostimulatory DC vaccines. In this context, we redesigned our currently clinically used DC vaccine generation protocol to enable transpresentation of interleukin- (IL-) 15 to IL-15Rβγ-expressing cells aiming at boosting the antitumor immune response. In this study, we demonstrate that upon electroporation with both IL-15 and IL-15Rα-encoding messenger RNA, mature DC become highly positive for surface IL-15, without influencing the expression of prototypic mature DC markers and with preservation of their cytokine-producing capacity and their migratory profile. Functionally, we show that IL-15-transpresenting DC are equal if not better inducers of T-cell proliferation and are superior in tumor antigen-specific T-cell activation compared with DC without IL-15 conditioning. In view of the clinical use of DC vaccines, we evidence with a time- and cost-effective manner that clinical grade DC can be safely engineered to transpresent IL-15, hereby gaining the ability to transfer the immune-stimulating IL-15 signal towards antitumor immune effector cells.